Public finances and state construction in the province of San Luis at the end of the Rosario period (1840-1850) - Harari, Emilio Fabián (2022)
The study of the trajectory of the provincial states, between 1820 and 1880, is crucial to understand the dynamics of a period considered until recently as a "transition". This article aims to reconstruct the state structure of a province not yet worked on: San Luis. For this, two significant variables are taken: the structure of state income and expenses and the material construction of the state in the province. The data show an excessive dependency from the Buenos Aires funds and a very precarious state construction, which would not allow the current hypotheses to be applied, which indicate the “autonomy” of these political formations.